Does Organizational Support Affect Employees’ Commitment to Implement Biogas Programs? - Syaifuddin, Syaifuddin (International Journal of Energy Economics and Policy, 2017)
The stakeholders must support the important process of generating renewable energy. One source of renewable energy is biogas produced from palm oil liquid waste. The organizations and employees’ support are expected to succeed biogas program and to generate the renewable energy. This research investigates organizational support and employees’ commitment in implementing biogas programs. The research was conducted in PTPN III Region of North Sumatera with a sample of 98 employees in eight areas proportionally. The explorative research aims to predict the effect of organizational support and employee’s commitment in implementing biogas program. The results show that the organizational support and employees’ commitment have either direct or indirect influence on biogas program. In conclusion, the biogas program needs organizational support and increased employees’ commitment so that it can be implemented in accordance with the intended purpose. Keywords: organizational support, commitment, biogas, renewable energy. JEL Classifications: O13, O14, O15